Local Culture in Indonesia As Risk of Child Sexual Abuse: A Systematic Review - Solehati, Tetti; Salsabila, Azzahra; Nurafni, Ratu; Millenika, Valencia Trie; Rindiarti, Nadia Amelia; Adila, Raisa; Hermayanti, Yanti; Kosasih, Cecep Eli; Mediani, Henny Suzana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Introduction: Sexual issues in Indonesia are never discussed openly in the family, one of the contributing factors is the presumption of taboo culture in the conversation of sexual topics.  This can be a risk of sexual abuse in children. Objective:  To identify the cultural diversity of Indonesia at risk of child sexual abuse. Method:  We conducted systematic reviews using PubMed, Science Direct, SpringerLink, EBSCO for the keywords "Indonesian culture" AND "child sexual abuse", then Google Scholar for keywords "“nilai-nilai” ATAU “budaya Indonesia” DAN “kekerasan seksual anak”. Literature searched follow inclusion criteria such as articles Indonesian and English, published in 2011-2021, Full-text, primary research, focusing on sexual abuse in children in terms of culture. After an initial selection of 4866 articles, then filtered and assessed using the JBI Tool so that 5 qualified articles were obtained. Results:  It was found that family factors, internal factors of perpetrators and victims, and external factors were cultural in Indonesia that are at risk of sexual abuse in children. Conclusion:  Based on the results of research it can be concluded that most cultures in Indonesia still consider it taboo to talk about sexual topics to children, so it can be a risk of sexual abuse in children. It is recommended that research be conducted to educate the problem of sexual abuse in children through a cultural approach involving family factors, internal factors, and external factors